2016
DOI: 10.1044/2016_ajslp-15-0030
|View full text |Cite
|
Sign up to set email alerts
|

A Usability Study of Internet-Based Therapy for Naming Deficits in Aphasia

Abstract: It is important to consider usability and the clinician's perspective in developing telepractice applications in speech-language pathology. Future directions include assessing the efficacy of remote treatment and collecting a larger sample of clinician data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 22 publications
4
38
0
7
Order By: Relevance
“…High levels of participant satisfaction are commonly found in telerehabilitation studies and have also been cited in other usability studies involving telerehabilitation (Simic et al, 2016). As in the Wade et al (2003) study participants in this study reported high levels of motivation to practice intensively and reported that this was achievable because they could access the therapy at home and had autonomy over their practice schedule.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…High levels of participant satisfaction are commonly found in telerehabilitation studies and have also been cited in other usability studies involving telerehabilitation (Simic et al, 2016). As in the Wade et al (2003) study participants in this study reported high levels of motivation to practice intensively and reported that this was achievable because they could access the therapy at home and had autonomy over their practice schedule.…”
Section: Discussionmentioning
confidence: 54%
“…As found by both Galliers et al (2012) and Simic et al (2016), the end-user design approach was successful in identifying features of the program that should be modified to enhance the usability and acceptability of the software for the users with aphasia. Furthermore, the collection of usability and acceptability data from both observation in a real world setting and interview provided additional confidence that the most important areas were identified for refinement.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations